[tex]9(t+1)\dfrac{\mathrm dy}{\mathrm dt}-7y=14t\implies\dfrac{\mathrm dy}{\mathrm dt}-\dfrac7{9(t+1)}y=\dfrac{14t}{9(t+1)}[/tex]
Look for an integrating factor [tex]\mu(t)[/tex]:
[tex]\ln\mu=\displaystyle-\frac79\int\frac{\mathrm dt}{t+1}=-\frac79\ln(t+1)\implies\mu=(t+1)^{-7/9}[/tex]
Multiply both sides by [tex]\mu[/tex]:
[tex](t+1)^{-7/9}\dfrac{\mathrm dy}{\mathrm dt}-\dfrac79(t+1)^{-16/9}y=\dfrac{14}9t(t+1)^{-16/9}[/tex]
Condense the left side as the derivative of a product:
[tex]\dfrac{\mathrm d}{\mathrm dt}\left[(t+1)^{-7/9}y\right]=\dfrac{14}9t(t+1)^{-16/9}[/tex]
Integrate both sides:
[tex](t+1)^{-7/9}y=\displaystyle\frac{14}9\int t(t+1)^{-16/9}\,\mathrm dt[/tex]
For the integral on the right, substitute
[tex]u=t+1\implies t=u-1\implies\mathrm dt=\mathrm du[/tex]
[tex]\displaystyle\int t(t+1)^{-16/9}\,\mathrm dt=\int(u-1)u^{-16/9}\,\mathrm du[/tex]
[tex]\displaystyle=\int\left(u^{-7/9}-u^{-16/9}\right)\,\mathrm du=\frac92u^{2/9}+\frac97u^{-7/9}+C[/tex]
[tex]\implies(t+1)^{-7/9}y=\dfrac{14}9\left(\dfrac92(t+1)^{2/9}+\dfrac97(t+1)^{-7/9}+C\right)[/tex]
[tex]\implies(t+1)^{-7/9}y=7(t+1)^{2/9}+2(t+1)^{-7/9}+C[/tex]
[tex]\implies y=7(t+1)+2+C(t+1)^{7/9}=7t+9+C(t+1)^{7/9}[/tex]
Given that [tex]y(0)=12[/tex], we get
[tex]12=9+C\implies C=3[/tex]
[tex]\implies\boxed{y(t)=7t+9+3(t+1)^{7/9}}[/tex]